Soil moisture content and its temporal stability in an arid aerial seeding afforestation area after 30 years vegetation restoration in China - Tang, Guodong; Zhao, Zhenyu; Jin, Xiaolin; Wu, Hao; Li, Jinrong (Frontiers in Forests and Global Change, 2024)
Soil moisture is a critical factor for vegetation restoration in arid regions. Poorly planned artificial sand-fixing vegetation systems often exacerbate soil moisture depletion, leading to further degradation. In this study, soil moisture content at various depths was continuously monitored from June to October 2023 in four key community plots-Corethrodendron scoparium, Calligonum mongolicum, Artemisia ordosica, and bare sand-in a 31-year-old revegetated area located on the northeastern edge of the Tengger Desert. We analyzed the distribution and dynamic changes of soil moisture across the different and evaluated its temporal stability. The representative soil moisture depth was determined by using the coefficient of determination (R²) and the Nash-Sutcliffe efficiency (NSE). The results showed significant differences in soil moisture among the four plots. The bare sand plot had the highest soil water storage in the 0-200 cm layer, at 46.37 mm. In contrast, the Corethrodendron scoparium, Calligonum mongolicum, and Artemisia ordosica plots had similar soil water storage values ranging from 33.50 to 33.67 mm, indicating that vegetation restoration has increased soil moisture absorption by an average of 27.4%. Analysis using relative difference and Spearman rank correlation methods revealed varying levels of temporal stability in soil moisture across different soil depths and plots. The Corethrodendron scoparium and bare sand plots showed higher temporal stability compared to the Calligonum mongolicum and Artemisia ordosica plots. The representative depths of temporal stability for the four plots were determined to be 100 cm, 150 cm, 20 cm, and 100 cm, respectively. These findings have significant theoretical implications for monitoring soil moisture and designing and managing artificial sand-fixing vegetation systems in arid regions.